Hadith #2168 - Sunan Abi Dawud - Abd al-Salam bin Mthr عبد السلام بن مطهر بن حسام; Ali bin al-Hakam al-Binani علي بن الحكم البناني; ibn Abbas; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Maqsim bin Bajra مقسم بن بجرة (Sunan Abi Dawud)
The Prophet (ﷺ) said about a man who has sexual intercourse with a menstruating woman: He should give one or half dinar as sadaqah.
Grade: Sahih

Hadith #2530 - Sunan Abi Dawud - Abd al-Salam bin Mthr عبد السلام بن مطهر بن حسام; Anas ibn Malik; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
A man emigrated to the Messenger of Allah (ﷺ) from the Yemen. He asked (him): Have you anyone (of your relatives) in the Yemen? He replied: My parents. He asked: Did they permit you? He replied: No. He said: Go back to them and ask for their permission. If they permit you, then fight (in the path of Allah), otherwise be devoted to them.
Grade: Sahih